Sigmoidal curves reflect impacts and dynamics of aquatic invasive species - Soto, Ismael; Ahmed, Danish A; Balzani, Paride; Cuthbert, Ross N; Haubrock, Phillip J (The Science of the total environment, 2023)
Identifying general patterns and trends underlying the impacts and dynamics of biological invasions has proven elusive for scientists. Recently, the impact curve was proposed as a means to predict temporal impacts of invasive alien species, characterised by a sigmoidal growth pattern with an initial exponential increase, followed by a subsequent rate of decline and approaching a saturation level in the long-term where impact is maximised. While the impact curve has been empirically demonstrated with monitoring data of a single invasive alien species (the New Zealand mud snail, Potamopyrgus antipodarum), broadscale applicability remains to be tested for other taxa. Here, we examined whether the impact curve can adequately describe the invasion dynamics of 13 other aquatic species (within Amphipoda, Bivalvia, Gastropoda, Hirudinea, Isopoda, Mysida, and Platyhelminthes) at the European level, employing multi-decadal time series of macroinvertebrate cumulative abundances from regular benthic monitoring efforts. For all except one tested species (the killer shrimp, Dikerogammarus villosus), the sigmoidal impact curve was strongly supported (R2 > 0.95) on a sufficiently long time-scale. For D. villosus, the impact had not yet reached saturation, likely reflecting the ongoing European invasion. The impact curve facilitated estimation of introduction years and lag phases, as well as parameterisation of growth rates and carrying capacities, providing strong support for the boom-bust dynamics typically observed in several invader populations. These findings suggest that impact can grow rapidly before saturating at a high level, with timely monitoring often lacking for the detection of invasive alien species post-introduction. We further confirm the applicability of the impact curve to determine trends in invasion stages, population dynamics, and impacts of pertinent invaders, ultimately helping inform the timing of management interventions. We hence call for improved monitoring and reporting of invasive alien species over broad spatio-temporal scales to permit further testing of large-scale impact consistencies across various habitat types.
Keywords: Amphipoda; Time series; Invasion curve; zvířata; zavlečené druhy; Introduced Species; Biological invasion; Impact prediction; plži; Population dynamics; Ecosystem; Animals; populační dynamika; ekosystém; Population Dynamics; Rivers; Gastropoda